2000
DOI: 10.1577/1548-8659(2000)129<0194:gpsaoo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Population Structure and Origin of Life History Types in Chinook Salmon in British Columbia, Canada

Abstract: We used protein electrophoresis to examine genetic population structure and origin of life history types of chinook salmon Oncorhynchus tshawytscha in British Columbia, Canada. Among 31 allozyme loci resolved in 91 samples from 63 populations of chinook salmon in rivers and hatcheries throughout British Columbia, population heterozygosities averaged 0.084 (range 0.048–0.108) and were typical of values for populations in other regions. A hierarchical gene diversity analysis indicated that 91.3% of the total all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
42
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 24 publications
6
42
2
Order By: Relevance
“…(A complete set of allelic frequencies can be retrieved by accessing the website http:// www.nwfsc.noaa.gov/publications/). The genotypic frequencies for these samples generally conform to Hardy-Weinberg expectations (Utter et al 1989;Bartley et al 1992;Waples et al 1993;Teel et al 2000), and the banding patterns conform to expectations based on subunit structure of the enzymes, indicating that the data generally meet the criteria Utter et al (1987) suggested for inferring a genetic basis for phenotypic variation of allozymes. In Chinook salmon, the duplicated loci sAAT-1,2*, sMDH-A1,2*, and sMDH-B1,2* are considered isoloci (Waples 1988).…”
Section: Genetic Datasupporting
confidence: 61%
See 2 more Smart Citations
“…(A complete set of allelic frequencies can be retrieved by accessing the website http:// www.nwfsc.noaa.gov/publications/). The genotypic frequencies for these samples generally conform to Hardy-Weinberg expectations (Utter et al 1989;Bartley et al 1992;Waples et al 1993;Teel et al 2000), and the banding patterns conform to expectations based on subunit structure of the enzymes, indicating that the data generally meet the criteria Utter et al (1987) suggested for inferring a genetic basis for phenotypic variation of allozymes. In Chinook salmon, the duplicated loci sAAT-1,2*, sMDH-A1,2*, and sMDH-B1,2* are considered isoloci (Waples 1988).…”
Section: Genetic Datasupporting
confidence: 61%
“…However, on a broader geographic scale it is apparent that the pattern of genetic/life-history relationships in Chinook salmon is more complicated than proposed by Healey or in other recent studies with a more restricted geographic scope (e.g., Teel et al 2000). First, the extremely divergent upper Willamette River populations suggest that Healey's hypothesis of only two major lineages may be too simplistic.…”
Section: Patterns Of Genetic and Life-history Differentiationmentioning
confidence: 90%
See 1 more Smart Citation
“…Yearling type smolts predominate in the North (north of 56°N), whereas sub-yearling smolts are almost exclusively distributed in the South (Healey 1991). The main exceptions are the Fraser and the Columbia River systems, as well as populations in northern Puget Sound where both types are found (Healey 1991, Teel et al 2000, Waples et al 2004.…”
Section: Open Pen Access Ccessmentioning
confidence: 99%
“…Yearling type smolts predominate in the North (north of 56°N), whereas sub-yearling smolts are almost exclusively distributed in the South (Healey 1991). The main exceptions are the Fraser and the Columbia River systems, as well as populations in northern Puget Sound where both types are found (Healey 1991, Teel et al 2000, Waples et al 2004.Recent studies have focused both on defining marine habitat use for juvenile Chinook salmon (Bi et al 2007, 2008, 2011a, Peterson et al 2010 and the relationship between variable ocean conditions and abundance, growth or condition (Wells et al 2008, MacFarlane 2010. The presence and abundance of Chinook salmon is negatively correlated with water temperature and depth, and positively correlated to various production indices such as chlorophyll (chl) a concentration and zooplankton (copepod) biomass (Brodeur et al 2000, Fisher et al 2007, Bi et al 2007, 2011a, Peterson et al 2010.…”
mentioning
confidence: 99%